2021
DOI: 10.1111/jfbc.13870
|View full text |Cite
|
Sign up to set email alerts
|

The interaction effect between tea polyphenols and intestinal microbiota: Role in ameliorating neurological diseases

Abstract: Tea polyphenols (TP) are one of the most functional and bioactive substances in tea.The interactions between TP and intestinal microbiota suggest that probiotics intervention is a useful method to ameliorate neurological diseases. Now, numerous researches have suggested that TP plays a significant role in modulating intestinal bacteria, especially in the area of sustaining a stable state of intestinal microbial function and abundance. Furthermore, homeostatic intestinal bacteria can enhance the immunity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 73 publications
1
7
0
Order By: Relevance
“…The stable and elastic symbiotic relationship between intestinal immune system and microflora affects host health [ 90 ]. Intestinal mucosal immune system is one of the components of intestinal microecology.…”
Section: Immunomodulatory Effects Of Tp-mediated Gut-lung Axis On Cov...mentioning
confidence: 99%
“…The stable and elastic symbiotic relationship between intestinal immune system and microflora affects host health [ 90 ]. Intestinal mucosal immune system is one of the components of intestinal microecology.…”
Section: Immunomodulatory Effects Of Tp-mediated Gut-lung Axis On Cov...mentioning
confidence: 99%
“…Contrarily, fecal microbiota coming from intact rats transplanted to chronically stressed rats significantly reduced depression- and anxiety-like behaviors and anhedonia, which was associated with the suppressed activation of glial cells and the NLRP3 inflammasome in the brain [ 69 ]. Interestingly, polyphenols may regulate the composition of the gut microbiota, promoting beneficial effects on the intestinal microbiota and inhibiting the proliferation of harmful bacteria; thereby maintaining intestinal health and ameliorating some neurological and neuropsychic disorders [ 70 , 71 ]. This is important because a correct structure of gut microbiota in addition to an anti-inflammatory effect of diverse molecules, including polyphenols, has been associated with its antidepressant-like effects [ 72 ].…”
Section: Biochemical and Pharmacological Activity Of Flavonoid Chrysinmentioning
confidence: 99%
“…The need for the development of standardized methods for determining the rate of consumption of AGE is rightly indicated. Numerous studies have shown that polyphenols largely determine the number, composition and condition of intestinal bacteria, which, in turn, modulate neurological diseases [ 214 ]. Polyphenols have not only antioxidant properties, but also the ability to protect proteins from glycation (antiglycating ability).…”
Section: Conclusion: Integrative Properties Of Albumin In Diagnostics and Therapymentioning
confidence: 99%